Increases in adult life expectancy in rural South Africa: valuing the scale-up of HIV treatment - Bor, Jacob; Bärnighausen, Till (Science, 2013)
The scale-up of antiretroviral therapy (ART) is expected to raise adult life expectancy in populations with high HIV prevalence. Using data from a population cohort of over 101,000 individuals in rural KwaZulu-Natal, South Africa, we measured changes in adult life expectancy for 2000-2011. In 2003, the year before ART became available in the public-sector health system, adult life expectancy was 49.2 years; by 2011, adult life expectancy had increased to 60.5 years—an 11.3-year gain. Based on standard monetary valuation of life, the survival benefits of ART far outweigh the costs of providing treatment in this community. These gains in adult life expectancy signify the social value of ART and have implications for the investment decisions of individuals, governments, and donors. Adult life expectancy has increased by 11 years in rural KwaZulu-Natal since the 2004 public-sector scale-up of HIV treatment.
Gesehen am 29.05.2017